IMPROVING THE STUDENT READING COMPREHENSION THORUGH QUANTUM TEACHING TECHNIQUE AT SECOND SEMESTER ISLAMIC STATE INSTITUTE - Heri Syahrizal Maron (Acitya: Journal of Teaching and Education, 2020)
This research attempted to improve students reading comprehension by applying the quantum teaching technique. This research employed a classroom action research design, and it was carried out in two cycles. The data of study were student’s reading comprehensionn which were collected by means of a reading comprehension test. The student’s reading comprehension were categorized into five categories, namely: very high, high, moderate, low and very low levels of comprehension. The student’s participation was obtained through class observations during the reading classes. The observation data were calculated and categorized high, moderate, and low categories. The results show that the use of quantum teaching technique could increase the student’s reading comprehension. Students who fell into very high and high reading categories increased from 17 students (cycle one) to 21 (cycle two); the number of students who belonged to moderate and low categories also slightly decreased from 14 in cycle one to 12 in cycle two. There was two students who were in the very low reading comprehension category in cycle one, but none was in cycle two. Furthermore, the use of quantum teaching technique has also encouraged students to participate actively during the reading classes. The average level of the student’s participation in the reading class process was moderate. In short, the use of quantum teaching technique in reading classes could improve not only the students reading comprehension but also their participate in reading class activity.